2016
DOI: 10.1111/and.12750
|View full text |Cite
|
Sign up to set email alerts
|

A potential mechanism associated with lead-induced testicular toxicity in rats

Abstract: This study was conducted to investigate the mechanism of lead (Pb)-induced testicular toxicity. We examined the impact of Pb toxicity on 17β-oestradiol (E2), oestrogen receptors (ERs) and aromatase P450 which are key factors in spermatogenesis. Treatment of rats with Pb acetate (PbAc, 50 mg/L in drinking water) significantly reduced sperm count, motility, viability and increased sperm abnormalities along with degenerative changes in seminiferous tubules and Leydig cells. Additionally, administration of PbAc re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 44 publications
(64 reference statements)
2
35
0
Order By: Relevance
“…57 Our findings are in agreement with others who reported downregulation of testicular steroidogenic enzymes by Pb exposure. 23,49,58 The reduced levels of these hormones in conjunction with the decreased expression of steroidogenic genes confirm the toxicity of Pb on endocrine and reproductive organs. 13,48 Interestingly, UMB prevented the negative impact of Pb on the pituitary-gonadal axis evidenced by the elevated serum FSH, LH and testosterone levels.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…57 Our findings are in agreement with others who reported downregulation of testicular steroidogenic enzymes by Pb exposure. 23,49,58 The reduced levels of these hormones in conjunction with the decreased expression of steroidogenic genes confirm the toxicity of Pb on endocrine and reproductive organs. 13,48 Interestingly, UMB prevented the negative impact of Pb on the pituitary-gonadal axis evidenced by the elevated serum FSH, LH and testosterone levels.…”
Section: Discussionmentioning
confidence: 79%
“…Our findings are in the line with the findings of other investigators who reported disrupted pituitary-gonadal axis by Pb exposure. 46,48,49 LH is an important stimulator for testosterone secretion from testicular Leydig cells and adequate amount of testosterone is essential for the structural and functional integrity of reproductive organs as well as to maintain the structure and function of male accessory glands. FSH secretion is necessary for the normal spermatogenesis as it stimulates the proliferation, maturation, and function of Sertoli cells to produce signals for the initiation and maintenance of germ cells.…”
Section: Discussionmentioning
confidence: 99%
“…The supernatants were used to measure the concentration of the lipid peroxidation biomarker malondialdehyde (MDA) and the activity of antioxidant enzymes superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPX) using commercial kits (Bio-Diagnostics Co, Cairo, Egypt) as previously described. 22 …”
Section: Methodsmentioning
confidence: 99%
“…Liver tissues were homogenized using cold PBS, followed by centrifugation at 5000 g for 15 min at 4°C. The supernatants were used to measure the concentration of the lipid peroxidation biomarker MDA and the activity of antioxidant enzymes SOD, CAT, and GPX using commercial kits (Biodiagnostics Co., Cairo, Egypt, and Randox Laboratories Ltd., Crumlin, UK) and as previously described [ 36 ].…”
Section: Methodsmentioning
confidence: 99%